The Influence of the Role of Intra-school Student Organizations on Students' Social Skills - Muhamad Yamin A-Maulud, Muhamad Yamin A-Maulud; Ade Suherman; Lili Dianah (Institut Pendidikan Indonesia, 2024)
This study aims to determine the effect of the role of intra-school student organizations (OSIS) on the development of students' social skills. This research was conducted at SMP Negeri 2 Tarogong Kidul involving OSIS members. The population in this study were active student council members with a total of 30 people. Thus, the sample used is cencus sampling, so the entire population is used as a sample. Researchers used quantitative-descriptive methods to describe the influence of the student council role on students' social skills. The collection techniques used are observation, distributing questionnaires, interviews, and literature studies. The data obtained through the distribution of questionnaires were processed using SPSS and analyzed using simple linear regression analysis. The results obtained are the role of OSIS in SMP Negeri 2 Tarogong Kidul is very good, which means that with the OSIS students are able to give their opinions about a program or problem that needs to be discussed. Likewise, the social skills that have been formed are very good, this is indicated by the ability to control language and expression in every situation that is being faced by students. The inhibiting factors for student council in developing social skills are the lack of social awareness of students, egoism, the influence of the environment outside of school, and the economic condition of students. Meanwhile, the supporting factors that encourage the development of social skills through OSIS are the participation of the OSIS supervisor to direct social activities and the willingness of students to be involved in the event. Based on the results of hypothesis testing, it was found that there was an influence of the role of intra-school student organizations on the development of student skills.